O Currículo da Escola do Campo: conhecimentos e saberes presentes no processo pedagógico nas classes multisseriadas - Santos, Gabriel Gomes dos (Brasil, 2021)
The present study deals with the teaching learning process in rural schools and the need to be discussed and reflected upon by all. Therefore, discussing strategies that improve rural education contributes to the articulation of meaningful learning and contextualized with reality. Therefore, the research aimed to analyze the educational reality of a rural school, as well as to experience the didactic and pedagogical process in multigrade classes. The research has a qualitative approach, of the participant and field research type, interviews were carried out addressing the curriculum, the pedagogical practices, planning, and the challenges faced; the descriptive analysis allowed us to go through the teachers' reports in the multigrade classrooms of the rural school. The research site was a school in the rural area of the city of Barreirinha, and the study subjects are two teachers who work in these schools. The analysis of the data showed the great need for continued education for teachers who work in these schools, because it was perceived that teaching methods are fragmented and do not allow the full development of students, being present a traditional teaching presented by teachers in the reports. Therefore, the research awakens to a new pedagogical practice, having as a resource the everyday life of the studies and the knowledge that is presented in the classroom.